Subtypes I and II of Ulva prolifera O.F. Müller: Dominant Green Tide Species in the Southern Yellow Sea and Their Responses to Natural Light and Temperature Conditions - Shuang Zhao; Jinlin Liu; Zhangyi Xia; Jingyi Sun; Jianheng Zhang; Peimin He (Biology)
This study systematically investigated two ecotypes of Ulva prolifera, the dominant species responsible for green tides in the Yellow Sea, classified as Subtype I (strain I08-1) and Subtype II (strain QD-7). Both subtypes produce positively phototactic biflagellate gametes with oval/pear-shaped morphology but exhibit distinct cellular dimensions. Subtype I gametes demonstrated significantly larger cell sizes, with long and short axes measuring 6.55 μm and 4.62 μm, respectively, compared to Subtype II’s dimensions of 6.46 μm (long axis) and 3.03 μm (short axis). Developmental analysis revealed striking morphological divergence at the 6-day germling stage: Subtype I attained an average length of 1301.14 μm, more than doubling Subtype II’s 562.25 μm. Superior growth kinetics were observed in Subtype I, exhibiting enhanced specific growth rates (SGRs) across multiple parameters—main stem length (8.58% vs. 3.55%), primary branch elongation (19.17% vs. 12.59%), main stem width expansion (17.29% vs. 5.00%), and biomass accumulation (41.90% vs. 40.96% fresh weight). Chlorophyll quantification confirmed significantly higher pigment content in Subtype I. Pre-co-culture photosynthetic profiling demonstrated Subtype I’s superior quantum efficiency (α = 0.077 vs. 0.045) with marked differences in regulated energy dissipation (YNPQ) and non-photochemical quenching (NPQ). Post-co-culture physiological adaptation was evident in Subtype II, showing significant elevation of non-regulated energy dissipation quantum yield (YNO) and eventual surpassing of maximum electron transport rate (ETRmax) compared to Subtype I. These findings establish that U. prolifera employs robust photoprotective and thermal adaptation strategies under natural photothermal conditions. Crucially, YNO-based analysis revealed Subtype II’s enhanced high-light protection mechanisms and superior adaptability to intense irradiance environments. This research elucidates ecotype-specific environmental adaptation mechanisms in U. prolifera, providing critical insights for optimizing green tide mitigation strategies and advancing ecological understanding of algal bloom dynamics.